Subgradient methods and consensus algorithms for solving convex optimization problems - Johansson, B.; Keviczky, T.; Johansson, M.; Johansson, K.H. (2008 47th IEEE Conference on Decision and Control, 2008)
In this paper we propose a subgradient method for solving coupled optimization problems in a distributed way given restrictions on the communication topology. The iterative procedure maintains local variables at each node and relies on local subgradient updates in combination with a consensus process. The local subgradient steps are applied simultaneously as opposed to the standard sequential or cyclic procedure. We study convergence properties of the proposed scheme using results from consensus theory and approximate subgradient methods. The framework is illustrated on an optimal distributed finite-time rendezvous problem.